2022
DOI: 10.1186/s13049-021-00990-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of personal protection equipment does not negatively affect paramedics’ attention and dexterity: a prospective triple-cross over randomized controlled non-inferiority trial

Abstract: Background The COVID-19 pandemic led to widespread use of personal protection equipment (PPE), including filtering face piece (FFP) masks, throughout the world. PPE. Previous studies indicate that PPE impairs neurocognitive performance in healthcare workers. Concerns for personnel safety have led to special recommendations regarding basic life support (BLS) in patients with a potential SARS-CoV-2 infection, including the use of PPE. Established instruments are available to assess attention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 29 publications
0
21
0
9
Order By: Relevance
“…In keeping with our findings of increased physical demand, performance, and effort in PPE teams, Chen et al reported that rescuers’ increases in heart rate, mean arterial pressure, and subjective fatigue scores were significantly more obvious with the use of PPE, which was associated with a significant decrease in effective chest compressions [ 8 ]. By contrast, Kienbacher et al were able to demonstrate increased attention when performing basic life support while attention and dexterity were not inferior when wearing PPE, including N95 masks [ 29 ]. However, in light of a PPE-related gradual decrease in effective chest compressions resulting from increased rescuers’ fatigue, our finding of too few change-overs in PPE teams is worrisome.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with our findings of increased physical demand, performance, and effort in PPE teams, Chen et al reported that rescuers’ increases in heart rate, mean arterial pressure, and subjective fatigue scores were significantly more obvious with the use of PPE, which was associated with a significant decrease in effective chest compressions [ 8 ]. By contrast, Kienbacher et al were able to demonstrate increased attention when performing basic life support while attention and dexterity were not inferior when wearing PPE, including N95 masks [ 29 ]. However, in light of a PPE-related gradual decrease in effective chest compressions resulting from increased rescuers’ fatigue, our finding of too few change-overs in PPE teams is worrisome.…”
Section: Discussionmentioning
confidence: 99%
“…As intervenções incluíram caminhada, (5,20) caminhada em esteira, (18,19) exercício intervalado de média a alta intensidade em cicloergômetro (6,12,16,21) e subir e descer escadas. (22)…”
Section: Seleção Dos Estudosunclassified
“…Apenas 8 dos 10 estudos incluídos nesta revisão forneceram dados suficientes para analisar PA, FC, FR e SpO 2 em intervenções aeróbicas com e sem máscaras N95/PFF2. (6,12,16,18,19,(21)(22)(23) Portanto, apenas esses 8 estudos foram incluídos em nossa meta-análise, num total de 166 voluntários. A diferença média padronizada variou de −0,32 a 0,17 para PA, de −0,27 a 0,13 para SpO 2 , de −0,10 a 0,27 para FC e de −0,16 a 0,28 para FR com um modelo de efeitos fixos e sem alterações estatisticamente significativas em nenhuma das variáveis.…”
Section: Meta-análiseunclassified
See 2 more Smart Citations